Odpowiedź :
1.)
Usuń nawiasy i zredukuj wyrazy podobne:
a). -2(3a+5b) + 3(4b - 6a) =-2*-3a +17b
b). -7 (x-3y + 1/7 z - 2) - 3(y+x+z) - 18y= -7*2x-14y+21/7z
Usuń nawiasy i zredukuj wyrazy podobne:
a). -2(3a+5b) + 3(4b - 6a) =-2*-3a +17b
b). -7 (x-3y + 1/7 z - 2) - 3(y+x+z) - 18y= -7*2x-14y+21/7z
ZAdanie 1/56
-6a -10b +12b -18a=-24a +2b
-7x+21y-z+14-3y-3x-3z-18y=-10x-4z +14
zadanie 1/86
2(a-a)
x(15+5)
bc(2/3-1/3)
x(6xb-3)
m(4mn+10)
a(4x-8y-4z)
y(6a-9b+12)
zadanie 2/87
A 4
B 1
C 5
D 2
E 3
-6a -10b +12b -18a=-24a +2b
-7x+21y-z+14-3y-3x-3z-18y=-10x-4z +14
zadanie 1/86
2(a-a)
x(15+5)
bc(2/3-1/3)
x(6xb-3)
m(4mn+10)
a(4x-8y-4z)
y(6a-9b+12)
zadanie 2/87
A 4
B 1
C 5
D 2
E 3